Tax Avoidance: Executive Character, Leverage, Audit Quality and Firm Size - Huda Trihatmoko; Ridarmelli; Admid Aisyah Amanah (Politeknik Negeri Madiun, 2025)
The purpose of this study is to ascertain how tax avoidance is impacted by executive character, leverage, audit quality, and firm size. The population of the manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the years 2016–2021 is used in this study. Purposive sampling is the sample selection technique employed in this quantitative study design. This study examines the effects of firm size, audit quality, executive character, and leverage on tax avoidance using panel data regression and a Random Effect Model (REM). The results of the study indicate that executive character and audit quality have a significant influence on tax avoidance practices. This finding indicates that executive personal characteristics, such as the tendency to take risks or be ethical, can influence a company's decision to conduct tax avoidance. In addition, good audit quality can suppress such practices by increasing transparency and accountability. On the other hand, leverage and company size variables do not show a significant influence on tax avoidance. This indicates that the amount of debt or company scale is not always a determining factor in tax avoidance decisions. Thus, this study provides important insights into internal and external factors of the company that influence the tax strategies implemented.